New double-stapling technique without staple-crossing line in laparoscopic low anterior resection: effort to reduce anastomotic leakage - Nam Seok Kim; Ji Hoon Kim; Yoon Suk Lee; In Kyu Lee; Won Kyung Kang (Annals of Coloproctology)
Purpose This study aimed to demonstrate the safety of new double-stapling technique (nDST), without a crossing line and dog ears, by comparing with conventional DST (cDST) in laparoscopic low anterior resection (LAR). Methods We retrospectively reviewed 98 consecutive patients who underwent laparoscopic LAR for rectal cancer from January 2018 to December 2020. The inclusion criterion was an anastomosis level below the peritoneal reflection and 4 cm above the anal verge. In the nDST group, the staple line of the linear cutter was sutured using barbed sutures to shorten the staple line before firing the circular stapler. Therefore, there were no crossing lines after firing the circular stapler. A 2:1 propensity score matching was performed between the cDST and nDST groups. Results After propensity score matching, 39 patients were in the cDST group and 20 were in the nDST group. There were no significant differences in patient demographics between the 2 groups. There was no difference in the total operation time between the cDST and nDST groups (124.0±26.2 minutes vs. 125.2±20.3 minutes, P=0.853). Morbidity rates were similar between the 2 groups (9 cases [23.1%] vs. 5 cases [25.0%], P=0.855). There was no significant difference in leakage rate (4 cases [10.3%] vs. 1 case [5.0%], P=0.847) and anastomotic bleeding rate (1 case [2.6%] vs. 3 cases [15.0%], P=0.211). Conclusion The nDST to eliminate the crossing line and dog ears in laparoscopic LAR is technically feasible and safe. However, more attention should be paid to anastomotic bleeding in such cases.